Infinitely Many Solutions for a Robin Boundary Value Problem - Aixia Qian; Chong Li (International Journal of Differential Equations)
By combining the embedding arguments and the variational methods, we obtain infinitely many solutions for a class of superlinear elliptic problems with the Robin boundary value under weaker conditions.